2021
DOI: 10.1177/0269216320986717
|View full text |Cite
|
Sign up to set email alerts
|

Practice review: Evidence-based quality use of corticosteroids in the palliative care of patients with advanced cancer

Abstract: Background: It would be unusual for a patient with advanced cancer not to be prescribed corticosteroids at some stage of their disease course for a variety of specific and non-specific indications. Aim: The aim of this practice review was to provide a pragmatic overview of the evidence supporting current practice and to identify areas in which further research is indicated. Design: A ‘state-of-the-art’ review approach was used to examine the evidence supporting the use of corticosteroids for the management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…A recent study from New Zealand suggested corticosteroids are largely prescribed based on anecdotal and experiential evidence rather than on robust research [ 98 ]. Further investigation into the specific reasons for prescribing dexamethasone in the Australian setting using audit or qualitative methods is warranted given potential harms, absence of evidence for prolonged use of dexamethasone and limited information on why prescribers choose this medication [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from New Zealand suggested corticosteroids are largely prescribed based on anecdotal and experiential evidence rather than on robust research [ 98 ]. Further investigation into the specific reasons for prescribing dexamethasone in the Australian setting using audit or qualitative methods is warranted given potential harms, absence of evidence for prolonged use of dexamethasone and limited information on why prescribers choose this medication [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, corticosteroids have become well established in the management of patients with cancer at several levels although primarily in the management of cancer-related complications or treatment side effects. Nonetheless, it should be underlined that the use of a number of therapeutic approaches using GCs [ 72 ] lack a solid scientific rationale even though the side effects of GCs treatment are well known. This is all the more important to keep in mind since the advent of immunotherapy, which is quickly becoming a leading component of therapy in the majority of cancers.…”
Section: Background: the Historical Role Of Glucocorticoids In Cancer...mentioning
confidence: 99%
“…However, the effect deteriorates during long-term use, and it is optimal to use for only shorter time-periods, e.g., 2 weeks. Interestingly, although the extensive use of corticosteroids, general guidelines for the use of this drug in palliative care is lacking [ 48 ]. Indeed, in two recent meta-analyses and reviews, it is shown that the evidence base for most indications of corticosteroids in palliative care were limited or non-existing [ 48 , 49 ].…”
Section: Corticosteroidsmentioning
confidence: 99%